ABCG2 regulated by MAPK pathways is associated with cancer progression in laryngeal squamous cell carcinoma - Xie, Jin (Am J Cancer Res, 2014)
ATP-binding cassette, subfamily G, member 2 (ABCG2) overexpression has been associated with multidrug resistance and cancer progression by promoting proliferation and/or suppressing apoptosis, but how this process happens remains to be determined. In this study, the roles and the mechanisms of ABCG2 in the progression of Laryngeal squamous cell carcinoma (LSCC) were investigated. We found that introduction of ABCG2 siRNA into Hep-2 and Hep-2T cells significantly enhanced the intracellular accumulation of mitoxantrone (MX). Down-regulation of ABCG2 by transient RNAi inhibited cell proliferation and blocked cell cycle progression by regulating the expression of cyclin D3 and p21 Cip1. ABCG2 silence also induced cell apoptosis by regulating the expression of surviving, bcl-2 and the cleavage of poly (ADP-ribose) polymerase (PARP) in Hep-2 and Hep-2T cells. ABCG2-specific inhibitor, fumitremorgin C (FTC), and mitogen-activated protein kinase (MAPK) pathway inhibitor, U0126, inhibited cell proliferation and promoted cell apoptosis by degrading endogenous ABCG2 in Hep-2T cells. Furthermore, inhibition of MAPK pathway by U0126 enhanced anti-cancer effects of MX in vivo. In conclusion, suppression of ABCG2 inhibits the procession of LSCC tumor growth by regulating cell proliferation and apoptosis. Our data also provide more evidence for the importance of the MAPK pathway as a suitable therapeutic target for LSCC.